EXPLORING CURRENTLY INVESTIGATED METHODS OF REGENERATIVE MEDICINE BASED THERAPIES FOR THE TREATMENT OF ACUTE KIDNEY INJURY - Krishnan, Anisha (Wake Forest University, 2026)
Acute kidney injury (AKI), most commonly a result of prolonged blood flow reduction, grows increasingly prevalent in hospitalized patient populations both within the United States and globally. Patients who have previously resolved AKI or who have sustained severe AKI are at a greater risk for developing chronic kidney conditions. Currently available therapies for chronic conditions, such as dialysis and transplantation, are not options for acute injury, and current pharmacological approaches include reno-protective anesthetic alternatives such as propofol, as well as small molecule therapeutics with anti-inflammatory or selective vasoconstrictive effects to treat AKI after the fact, but with no documented functional restorative effects. For this reason, regenerative medicine-based therapies are a necessary approach in order to both mitigate damage and return normal tissue function. Here, we review the currently investigated regenerative medicine therapies to provide a comprehensive understanding of the state of latest progress within the field to better inform future research directions.